1974
DOI: 10.1073/pnas.71.3.858
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Allosterism in In Vitro DNA Synthesis on RNA Templates

Abstract: Hemoglobin mRNA and (rA)n. (dT)lo have been used as primer-templates in a kinetic study of DNA synthesis with Escherichia coli DNA polymerase I (DNA nucleotidyl transferase, EC 2.7.7.7) and Mason-Pfizer monkey virus reverse transcriptase (RNA-directed DNA polymerase). The rate versus enzyme concentration curve is sigmoidal and is consistent with a cooperative phenomenon. The results could be interpreted in terms of the formation of an active complex containing enzyme dimers (or oligomers) on the primer-templat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The sigmoidal nature of the plots shown in Figure S5 b,cindicates that the VE CeO 2 NPs act as multivalent or cooperative catalysts. [12] At certain concentrations,t he interactions between the nanoparticles appear to play an important role in enhancing the rate of the reaction. Such catalyst-dependent sigmoidal behavior has been ascribed to the formation of enzyme dimer or oligomers.…”
Section: Methodsmentioning
confidence: 99%
“…The sigmoidal nature of the plots shown in Figure S5 b,cindicates that the VE CeO 2 NPs act as multivalent or cooperative catalysts. [12] At certain concentrations,t he interactions between the nanoparticles appear to play an important role in enhancing the rate of the reaction. Such catalyst-dependent sigmoidal behavior has been ascribed to the formation of enzyme dimer or oligomers.…”
Section: Methodsmentioning
confidence: 99%
“…the active site may be altered by interaction of the effector tRNA at a site on the enzyme which is not accessible in the oligomer. We have presented evidence for allosteric effects in the E. coli Pol I system (20).…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics of RNA directed DNA synthesis catalyzed by Mason-Pfizer monkey virus reverse transcriptase and by E. coli DNA polymerase I were recently studied by Cavalieri et al (1) using both homopolymers and heteropolymers as templates. A homopolymer, usually oligo(dT)10, was used as a primer.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of synthesis also was Nucleic Acids Research found to increase sigmoidally as the concentration of enzyme was increased. Their data, obtained by using trichloroacetic acid (TCA) precipitation to isolate the product DNA, were interpreted as evidence for allosterism during reverse transcription (1). If Enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation